Optimizing Digital Marketing and Pricing to Strengthen Consumer Loyalty in Startup Businesses - Rizky Fatmawati; Eka Rahma Salsabila (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to evaluate the implementation of digital marketing strategies and pricing management to strengthen consumer loyalty in startup businesses. The background of this study is based on the increasing use of the internet and social media as promotional tools that are not being maximized by startup businesses. The study uses a qualitative descriptive approach with data collection methods through observation, interviews, and documentation of startup business actors. The results show that the use of integrated digital marketing and price optimization through behavioral economics on startup business platforms such as Shopee and Blibli has a positive impact on increasing consumer loyalty. The novelty of this study lies in the integrative approach that combines behavioral psychology-based pricing strategies with digital marketing techniques to build consumer loyalty among startuppreneurs. This approach has not been widely explored in the context of startups in developing countries, particularly Indonesia, thus offering a new perspective relevant to sustainable digital business models.